On the Spectral Theory of Generalized Toeplitz Kernels - Chernobai, O. B. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We give a criterion for the denseness of the Fourier transform in the space L 2 associated with spectral representation of positive-definite Toeplitz kernels.